2017
DOI: 10.12972/kjhst.20170045
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Shading Net Color on Phytochemical Contents in Two Chili Pepper Hybrids Cultivated Under Greenhouse Conditions

Zsuzsa Nagy,
Hussein Daood,
Andárs Neményi
et al.

Abstract: The objective of this study was to understand the combined effect of shading treatment and harvest time on pungency, ascorbic acid content, market-quality pepper yield, and photosynthetic activity in a yellow 'Star Flame' and 'Fire Flame' F1 hybrid pepper cultivar (Capsicum annuum). Plants were cultivated in a greenhouse under white, red, and green shading nets and compared to those grown under unshaded control conditions. The ascorbic acid and pungency parameters were analyzed by high-performance liquid chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The environmental conditions in which chili is cultivated or the inherent genetic characteristics of each cultivar can be attributed to the variances in capsaicinoid quantity (Table 7) (Hamed et al., 2019). The phytochemical contents of the hybrid chili peppers were significantly influenced by shading net color, with varying colors corresponding to different quantities of phytochemicals (Nagy et al., 2017a). The total capsaicinoids, vitamin C, and relative chlorophyll content were significantly impacted by shading, with shaded plants exhibiting lower amounts than unshaded plants (Zsuzsa, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The environmental conditions in which chili is cultivated or the inherent genetic characteristics of each cultivar can be attributed to the variances in capsaicinoid quantity (Table 7) (Hamed et al., 2019). The phytochemical contents of the hybrid chili peppers were significantly influenced by shading net color, with varying colors corresponding to different quantities of phytochemicals (Nagy et al., 2017a). The total capsaicinoids, vitamin C, and relative chlorophyll content were significantly impacted by shading, with shaded plants exhibiting lower amounts than unshaded plants (Zsuzsa, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…(Agyemang Duah et al, 2021) Stomatal density Shading increase stomatal density. (Nagy et al, 2017a) and total dry weight of chili were observed under the 25% shading (Table 6) (Stamps, 2009). Chili pepper plants' yields tended to decrease under a shade cloth with 50% light exclusion (Sumiyati et al, 2021).…”
Section: Parameters Studied Influences Referencesmentioning
confidence: 98%
See 1 more Smart Citation
“…Plant height (cm) Nagy et al (2017), Ibrahim (2021) and Zisis et al (2019), who proved the positive role of shading in improving the growth and yield of sweet pepper and eggplant crops.…”
Section: Characteristicsmentioning
confidence: 99%
“…Nagy et al [35] conducted a study of the production of pepper plants grown in a greenhouse under white, red and green shading and determined that the content of ascorbic acid increased even more in the fruits of plants grown with white shading.…”
Section: Meshmentioning
confidence: 99%